2006
DOI: 10.1176/ajp.2006.163.12.2096
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Olanzapine Versus Risperidone for the Treatment of First-Episode Schizophrenia: 4-Month Outcomes

Abstract: Clinical outcomes with risperidone were equal to those with olanzapine, and response may be more stable. Olanzapine may have an advantage for motor side effects. Both medications caused substantial rapid weight gain, but weight gain was greater with olanzapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 31 publications
(29 reference statements)
6
71
0
Order By: Relevance
“…A high rate of akathisia was seen with ziprasidone in EUFEST (Kahn et al, 2008) and concomitant medication use suggested a slight EPS advantage for quetiapine over olanzapine (McEvoy et al, 2007) and olanzapine over risperidone (Crespo-Facorro et al, 2006Robinson et al, 2006). These tentative differences are consistent with those seen in large meta-analyses, predominantly in patients with chronic schizophrenia (e.g.…”
Section: Rates Of Epssupporting
confidence: 75%
See 3 more Smart Citations
“…A high rate of akathisia was seen with ziprasidone in EUFEST (Kahn et al, 2008) and concomitant medication use suggested a slight EPS advantage for quetiapine over olanzapine (McEvoy et al, 2007) and olanzapine over risperidone (Crespo-Facorro et al, 2006Robinson et al, 2006). These tentative differences are consistent with those seen in large meta-analyses, predominantly in patients with chronic schizophrenia (e.g.…”
Section: Rates Of Epssupporting
confidence: 75%
“…Four trials were open (Crespo-Facorro et al, 2006Glenthoj et al, 2007;Kahn et al, 2008;Robinson et al, 2006) though raters were blind to treatment in one (Robinson et al, 2006). The remaining seven trials were double blind.…”
Section: Trial Design Including Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…All but two patients had participated in a clinical treatment trial comparing the efficacy of risperidone vs olanzapine. Further details regarding the ascertainment of patients and the clinical trial are available in Robinson et al (2006). In the present study we defined recent onset as having a duration of illness from the index episode or entry into the clinical trial to the MRI exam of 4.25 years or less (median ¼ 79 weeks, mode ¼ 0, range ¼ 0-4.25 years).…”
Section: Subjectsmentioning
confidence: 99%